2003
DOI: 10.1021/jf020936m
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols and Antioxidant Capacity of Vegetables under Fresh and Frozen Conditions

Abstract: The phenolic and oxygen radical absorbance capacity (ORAC) values have been measured in six fresh and frozen vegetables (beet green, spinach, broccoli, carrot, onion, and celery) from the same cultivar by analyzing the whole juice (WJ) and the acetonic extract of the squeezed pulp. To exploit the effect of the acid environment on the stability and recovery of the phenolics, perchloric acid (PCA) was added directly to WJ and to the pulp before the extraction with acetone. In both fresh and frozen vegetables, PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
76
5
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(97 citation statements)
references
References 32 publications
8
76
5
2
Order By: Relevance
“…This is ascribed to the fact that different plants have distinct compound contents, with several structures, thus offering different protective mechanisms at different levels (Chu, Sun, Wu, and Liu, 2002;Ninfali and Bacchiocca, 2003). Among phtyochemicals, phenolic compounds and organic acids may exert a protective role against various diseases, due to their antioxidant potential (Silva et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This is ascribed to the fact that different plants have distinct compound contents, with several structures, thus offering different protective mechanisms at different levels (Chu, Sun, Wu, and Liu, 2002;Ninfali and Bacchiocca, 2003). Among phtyochemicals, phenolic compounds and organic acids may exert a protective role against various diseases, due to their antioxidant potential (Silva et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Cauliflower has been assayed for the ability to scavenge DPPH Å and ABTS Å+ , as well as for ferric reducing efficiency and ability to inhibit lipid peroxidation (Llorach, Espín, Tomás-Barberán, & Ferreres, 2003). The oxygen radical absorbance capacity values have been measured in broccoli (Kurilich, Jeffery, Juvik, Wallig, & Klein, 2002;Ninfali & Bacchiocca, 2003). To find the antiradical activity of white cabbage, hydroxyl radical was used (Racchi et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In traditional medicine, celery has been used to treat asthma, bronchitis, spleen, and liver diseases (Singh & Handa 1995). Recently, there has been a growing interest in the plant for its healthbeneficial activities, such as antioxidant activities (Ninfali & Bacchiocca 2003), anti-inflammatory activity (Ovodova et al 2009), anticancer activities (Sultana et al 2005), anti-hyperlipidaemic effect (Tsi & Tan 2000;Iyer & Patil 2011), and so on. Numerous studies have confirmed that flavonoids consist of a common basic structure comprising two aromatic rings linked by three carbons that form an oxygenated heterocyclic compound, and phenol compounds are the main antioxidant substance which can promote the human health through reducing oxidative damage (Wang & Stoner 2008;Mousavinejad et al 2009).…”
mentioning
confidence: 99%